Improved Method for Obtaining of Arctigenin from Arctium Lappa L. and its Antiproliferative Effect on Human Hepatocarcinoma HepG2 Cells - Teixeira, Renan S.; Carvalho, Paulo H.D.; Aguiar, Jair A.K.; Medeiros, Valquíria P.; Da Silva Filho, Ademar A.; Nascimento, Jorge W.L. (Current Bioactive Compounds, 2020)
Background: Arctigenin is a lignan found in Arctium lappa L. (Asteraceae) that displays anti-inflammatory activities. Previous studies showed that the crude extract of A. Lappa has antitumor activity in human liver carcinoma, lung and stomach cancer cells. The aim of this study was to obtain arctigenin from A. lappa L., as well as to evaluate its antiproliferative effects in cells of liver carcinoma (HepG2) and fibroblasts (NIH/3T3). Methods: Arctigenin was obtained from the hydrolysis of arctiin, which was isolated from the crude extract of A. lappa. The effects of arctigenin and arctiin on HepG2 cell viability and cell adhesion were analyzed by MTT method. Adhesion assay was also carried out to evaluate the antitumor activity. Results: Our results showed that the analytical process to obtain arctigenin was fast and easy. In vitro experiments showed that arctigenin (107-269 μM) decreased HepG2 cells viability and did not cause cytotoxicity on NIH/3T3 cells. Arctigenin (27-269 μM) demonstrated anti-adhesion in HepG2 cells in a concentration-dependent manner, when compared with control. Conclusion: These results suggest a promising pharmacological activity for arctigenin as an antiproliferative compound.
Keywords: MTT